2022
DOI: 10.1007/s40747-022-00721-w
|View full text |Cite
|
Sign up to set email alerts
|

New extension of ordinal priority approach for multiple attribute decision-making problems: design and analysis

Abstract: The selection and assessment process of appropriate robots became a more complex and complicated task due to various available alternatives and conflicting attributes which must take into consideration. Also, uncertainty which exists usually in the selection process is an unavoidable component that needs to be thoughtfully measured and traditional multi-attribute decision-making approaches failed to deal precisely with it. Since almost all decisions originate from subjective ordinal preferences, handling uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Since the last few years, the researchers have endeavoured to explore its capability in solving diverse MCDM problems, like selection of healthcare supplier (Quartey-Papafio et al ., 2021), construction sub-contractor (Mahmoudi and Javed, 2022), project portfolio (Mahmoudi et al ., 2022a), transportation planning strategy (Pamucar et al ., 2022), road maintenance strategy (Bouraima et al ., 2022), distributed ledger technology (Sadeghi et al ., 2022a) and so on. Recently, it has also been successfully combined with TOPSIS for project selection (Mahmoudi et al ., 2021a), and shortlising of automotive parts suppliers (Bah and Tulkinov, 2022); data envelopment analysis (DEA) for supplier performance assessment (Mahmoudi et al ., 2022b); FST for selection of resilient suppliers selection (Mahmoudi et al ., 2022c), blockchain technology selection in construction organizations (Sadeghi et al ., 2022b) and appraising construction suppliers (Mahmoudi et al ., 2022d); neutrosophic fuzzy set for industrial robot selection (Abdel-Basset et al ., 2022); rough set theory for sustainable mining (Deveci et al ., 2022); and grey system theory to evaluate low-carbon sustainable technologies in agriculture (Shajedul, 2021), sustainable supplier selection for construction megaprojects (Mahmoudi et al ., 2021b) and identification of barriers to electric vehicle adoption (Candra, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Since the last few years, the researchers have endeavoured to explore its capability in solving diverse MCDM problems, like selection of healthcare supplier (Quartey-Papafio et al ., 2021), construction sub-contractor (Mahmoudi and Javed, 2022), project portfolio (Mahmoudi et al ., 2022a), transportation planning strategy (Pamucar et al ., 2022), road maintenance strategy (Bouraima et al ., 2022), distributed ledger technology (Sadeghi et al ., 2022a) and so on. Recently, it has also been successfully combined with TOPSIS for project selection (Mahmoudi et al ., 2021a), and shortlising of automotive parts suppliers (Bah and Tulkinov, 2022); data envelopment analysis (DEA) for supplier performance assessment (Mahmoudi et al ., 2022b); FST for selection of resilient suppliers selection (Mahmoudi et al ., 2022c), blockchain technology selection in construction organizations (Sadeghi et al ., 2022b) and appraising construction suppliers (Mahmoudi et al ., 2022d); neutrosophic fuzzy set for industrial robot selection (Abdel-Basset et al ., 2022); rough set theory for sustainable mining (Deveci et al ., 2022); and grey system theory to evaluate low-carbon sustainable technologies in agriculture (Shajedul, 2021), sustainable supplier selection for construction megaprojects (Mahmoudi et al ., 2021b) and identification of barriers to electric vehicle adoption (Candra, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Ataei et al (2020) proposed the OPA and compared it with six other models; AHP, BWM, TOPSIS, VIKOR, PROMETHEE, and QUALIFLEX (see the last row of Table 1 for full names). Their results, and those of succeeding studies (Abdel-Basset et al, 2022;Pamucar et al, 2022;Quartey-Papafio et al, 2021), revealed that the methodology of OPA enjoys several benefits compared with other models. For instance, it has been shown that the OPA does not require a pairwise comparison matrix, normalization of input, and averaging methods for aggregating experts' opinions.…”
Section: Introductionmentioning
confidence: 93%
“…Pamucar et al (2022) also extended OPA in fuzzy environment to prioritize transport planning strategies. Abdel-Basset et al (2022) extended OPA under neutrosophic environment for evaluation of robots.…”
Section: Grey Ordinal Priority Approachmentioning
confidence: 99%